Stakeholder Perspectives on e-Health Implementation in Armenia - Chukwuma, Adanna; Koshkakaryan, Marianna (World Bank, Washington, DC, 2018)
There is general recognition across stakeholders in Armenia that the e-health system can facilitate exchange of clinical and non-clinical information, transparency and accountability in service provision, and support for monitoring and evaluation. By tracking patient movement across health facilities, the e-health system links budgetary allocations to service use, enabling efficiency and supporting performance-based financing. However, scale-up of the e-health system has presented financial, technical, and organizational challenges that have negative implications for the sustainability of the system, efficient health care delivery, and the system’s ability to meet informational requirements for health decision-making. There are opportunities to iteratively adapt the e-health system in Armenia through a systematic assessment of the e-health system scale-up experience and through regular and structured interactions between the private operator of the e-health system, key stakeholders involved in the implementation of the e-health system, and policy makers that can facilitate the adoption of needed changes. The Armenian experience of implementing an integrated health information system provides useful lessons for improving the functionality of the current system and for adopting technologies to improve health systems more generally. To encourage facilities to continue to use the e-health system, there is an immediate need for financial support for the associated recurrent costs for maintaining the e-health system and technical assistance, including training and user manuals, to guide everyday use by medical practitioners.